2006
DOI: 10.1152/ajpendo.00166.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GH and/or sex steroids on circulating IGF-I and IGFBPs in healthy, aged women and men

Abstract: . Effects of GH and/or sex steroids on circulating IGF-I and IGFBPs in healthy, aged women and men. Am J Physiol Endocrinol Metab 290: E1006 -E1013, 2006. First published January 3, 2006 doi:10.1152/ajpendo.00166.2005.-Circulating GH, IGF-I, IGFBP-3, and sex steroid concentrations decrease with age. GH or sex steroid treatment increases IGFBP-3, but little is known regarding the effects of these hormones on other IGFBPs. We assessed the effects of 26 wk of administration of GH, sex steroids, or GH ϩ sex stero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 79 publications
2
27
0
Order By: Relevance
“…This finding is largely in accordance with previous clinical studies of healthy subjects and of GHD patients on GH treatment, demonstrating that IGFBP-4 and IGFBP-5 levels are influenced by the GH/IGF-I axis [21,22,32,33].…”
Section: Ghsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is largely in accordance with previous clinical studies of healthy subjects and of GHD patients on GH treatment, demonstrating that IGFBP-4 and IGFBP-5 levels are influenced by the GH/IGF-I axis [21,22,32,33].…”
Section: Ghsupporting
confidence: 92%
“…In a study on healthy, aged women and men, IGFBP-4 levels were unaffected after 26 weeks of GH treatment, whereas IGFBP-5 increased by 20% in men after GH. The weekly GH dose in that study was, however, approximately only one-sixth of the dose per kg and week used in our study [32].…”
Section: Ghmentioning
confidence: 74%
“…Munzer et al 54 demonstrated that hormone administration increased IGFBP3 and IGFBP5 levels. IGFBP3 is the most abundant circulating IGF-binding protein that inhibits cell growth and induces apoptosis by both IGF-I-dependent and IGF-I-independent pathways in many cancers, including prostate cancer.…”
Section: Growth Factorsmentioning
confidence: 99%
“…[52][53][54][55][56] Animal experiments demonstrate that tumor growth can be inhibited by disrupting IGF-I signaling pathways 53 and in a nested case-control study using data derived from the Physicians' Health Study cohort it was demon strated that increasing plasma levels of IGF-I were directly linked to increasing prostate cancer risk. 52 After adjusting for IGF-binding proteins (such as IGFBP3), men with a serum PSA level >4 ng/ml in combination with the highest quartile of IGF-I had a 17.5-fold risk of prostate cancer.…”
Section: Growth Factorsmentioning
confidence: 99%
“…Taken together, these data suggest that in addition to normal aging, sleep disturbances such as sleep apnea may substantially affect GH secretion and action, and thereby, have additional impact on the potential effects of CPAP treatment. Several studies have reported a sexual dimorphic interaction of GH axis activation with sleep (22)(23)(24), and both GH administration to healthy old persons (25,26) and GH therapy in patients with adult GHD syndrome (27) revealed that changes in LBM or adipose tissue depended on sex.…”
Section: Introductionmentioning
confidence: 99%